2015
DOI: 10.3324/haematol.2014.113803
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G expression levels influence the tolerogenic activity of human DC-10

Abstract: ABSTRACTand CD8 low suppressor T cells, 25 interleukin-10 (IL-10)-producing T regulatory type 1 (Tr1) cells, DC-10 are a subset of human tolerogenic DC that are present in vivo [27][28][29] and can be differentiated in vitro by culturing monocytes in the presence of IL-10. DC-10 secrete IL-10, are CD11c + , express CD14, CD16, HLA-G and ILT4 and, although not activated, display a mature phenotype, being CD86+ and HLA-DR + . The secretion of IL-10 and the expression of membrane-bound HLA-G and ILT4 are critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 55 publications
6
52
2
Order By: Relevance
“…Furthermore, Tr1 cells are reported to be induced at mucosal sites in response to Ag stimulation in the presence of IL-10. We observed that IL-10-deficient DCs promoted IL-10-secreting CD49b + Treg cell expansion in several lymphoid organs of wild-type animals, suggesting that, in contrast to Tr1 cells (64) + Treg cells and thus might also play an important role in the suppressive function of CD49b + Treg cells. Furthermore, CD103 expression could also be implicated in their suppressive function as its expression was shown to be responsible for the retention of Treg cells in inflamed tissue by interaction with its ligand E-cadherin (65,66).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, Tr1 cells are reported to be induced at mucosal sites in response to Ag stimulation in the presence of IL-10. We observed that IL-10-deficient DCs promoted IL-10-secreting CD49b + Treg cell expansion in several lymphoid organs of wild-type animals, suggesting that, in contrast to Tr1 cells (64) + Treg cells and thus might also play an important role in the suppressive function of CD49b + Treg cells. Furthermore, CD103 expression could also be implicated in their suppressive function as its expression was shown to be responsible for the retention of Treg cells in inflamed tissue by interaction with its ligand E-cadherin (65,66).…”
Section: Discussionmentioning
confidence: 81%
“…DC-10 secrete IL-10 in the absence of IL-12 and express the tolerogenic molecules ILT-4 and HLA-G . Resting and activated (Amodio and Gregori, 2012) DC-10 efficiently promote the differentiation of Tr1 cells from naive CD4 + T cells in vitro, which requires IL-10 production and expression of ILT-4 and HLA-G (Amodio et al, 2015;Gregori et al, 2010).…”
Section: Identification Of Tr1 Cellsmentioning
confidence: 99%
“…generated in vitro can be purified from bulk cultures using CD49b and LAG-3 antibodies (Amodio et al, 2015;Gagliani et al, 2013b;Mfarrej et al, 2017;Petrelli et al, 2015). The frequency of CD4 + CD45RA -CD49b + LAG-3 + cells correlates with the expression of IL-10 in human (Amodio et al, 2015;Mfarrej et al, 2017;Petrelli et al, 2015;Sutavani et al, 2013;Tousa et al, 2017;Yao et al, 2015;Tousa et al, 2017), and with induction of immunological tolerance in different preclinical and clinical settings Gagliani et al, 2013b;Kim et al, 2018;Koch et al, 2015;Zhu et al, 2018). Using single-cell mass cytometry, we have shown that CD49b and LAG-3 were sufficient to identify a population of CD4 + CD45RAcells, which is distinct from Th1, Th2, Th17, Tfh, and Treg cells.…”
Section: Phenotype Of Murine and Human Tr1 Cellsmentioning
confidence: 99%
“…Despite the presence of IL-10 during differentiation, DC-10 are mature myeloid cells that express CD86 and HLA-DR. DC-10 also express the tolerogenic molecules immunoglobulin-like transcript (ILT)2, ILT3, ILT4, and HLA-G [24]. The high expression levels of HLA-G and the high IL-10/IL-12 production ratio render DC-10 potent inducers of allo-specific Tr1 cells [24,83]. The clinical use of DC-10 relies on this latter feature, and clinical-grade protocols for the induction of allo-specific Tr1 cells, suitable for cell therapy, using DC-10 have been developed [84,85].…”
Section: Dcs As Tolerogenic Cell Productmentioning
confidence: 99%